The Representation Of Women's Resistance In The Film “Perempuan Tanah Jahanam” - Nindi putri; Endang, Anis; Risdiyanto, Bayu (Universitas Dehasen Bengkulu, 2024)
This study was conducted to analyze the representation of resistance by women in the horror film